2003
DOI: 10.1021/jp0272318
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Excited States of the Carotenoid Peridinin in Polar Solvents:  Dependence on Excitation Wavelength, Viscosity, and Temperature

Abstract: The dynamics of the excited states of the carotenoid peridinin in polar solvents were studied using femtosecond transient absorption spectroscopy in the spectral range of 500−1900 nm. A broadening of the absorption spectrum in polar solvents is caused by a distribution of conformers having different ground-state properties. In addition, the dependence of the peridinin lifetime on the excitation wavelength reveals that two peridinin forms coexist in protic solvents, where a “red”-absorbing form is produced by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
353
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 140 publications
(392 citation statements)
references
References 29 publications
39
353
0
Order By: Relevance
“…In these regards, it might be rational to assign the origin of band 1 to the S 0 → S 2-ICT transition. This assignment is consistent with the previous reports [7,9,25] and supports the idea by Zigmantas et al who suggested the presence of 'red' peridinin that has enhanced CT character [11]. A number of previous studies on peridinin showed importance of conformational disorder in explanation of excited-state properties.…”
Section: Mndo-psdci Calculationsupporting
confidence: 93%
See 1 more Smart Citation
“…In these regards, it might be rational to assign the origin of band 1 to the S 0 → S 2-ICT transition. This assignment is consistent with the previous reports [7,9,25] and supports the idea by Zigmantas et al who suggested the presence of 'red' peridinin that has enhanced CT character [11]. A number of previous studies on peridinin showed importance of conformational disorder in explanation of excited-state properties.…”
Section: Mndo-psdci Calculationsupporting
confidence: 93%
“…They believe this is one of the origins of efficient energy-transfer from the S 2 state of Per to chlorophyll a. Linden et al carried out experimental [10] and theoretical [6] studies and found the S 2-ICT state close in energy to the one-photon allowed 1 1 B u + state. Zigmantas et al showed that excitation of peridinin to the very red edge of its S 0 → S 2 absorption generates excited-state dynamics different from that produced after excitation at the absorption maximum [11]. This effect was assigned to excitation of the S 2 state of a specific 'red' peridinin having a CT character.…”
Section: Introductionmentioning
confidence: 99%
“…It can be speculated that the cyclopentanone ring is involved in this localization step. This assumption is likely because other groups having observed a decay pattern very similar to the one reported here, made their observations in peridinin, a carotenoid highly substituted and possessing a cyclopentanone ring as well [99][100][101][102]. This assumption is further corroborated by experimental results obtained on magnesium octaethylporphyrin (MgOEP) (data not shown) as MgOEP, in contrast to the structurally similar PChla, which in addition has an attached cyclopentanone ring to the porphyrin macrocycle, does not exhibit any significant excited-state dynamics, when directly being promoted into the Q 00 band [22].…”
Section: Protochlorophyllide Asupporting
confidence: 81%
“…Therefore, focusing on the dynamics occurring within the first 12.1 ps after photoexcitation, PChlamethanol exhibits a rise component in addition to the primary decay, while the kinetics of PChla-glycerol can be accounted for by the 12.1-ps decay only. From the characteristic time scales of PChla-glycerol being significantly longer than the corresponding time constants obtained for PChla-methanol, it can be inferred that the increased viscosity affects the rate of the corresponding relaxation processes [19,[102][103][104][105][106][107]. As the nuclear motion of the vibrating molecule is slowed down in the highly viscose solvent the rate of energy dissipation associated with the shortest time scale decreases.…”
Section: Protochlorophyllide Amentioning
confidence: 89%
“…2B). Although it is possible to separate the S 1 -like and ICTlike transitions in transient absorption spectra, the S 1 and ICT states of carbonyl carotenoids are strongly coupled in the S 1 ∕ICT state (32,35), and the intensity of the ICT-like transition is a measure of a degree of charge-transfer character of the S 1 ∕ICT state. It was recently shown that the intensity of the ICTlike transition significantly increases if a single conjugated carbonyl group of a carotenoid is positioned in an s-trans configuration with respect to the main conjugated backbone (36); however, this is not the case for spheroidenone in solution where the carbonyl group is in an s-cis orientation as evidenced by molecular modeling showing that s-cis configuration is far more stable (Fig.…”
Section: Resultsmentioning
confidence: 99%